Computational Studies of Super-B as Anodes for AM (Li, Na, and K) Ion Batteries. Issue 9 (1st September 2022) - Khan, Muhammad Isa; Anwar, Maida; Majid, Abdul; Shakil, Muhammad; Rizwan, Muhammad
Abstract : Energy storage systems have recently become the focus of current research for mankind's future. This study, as per the features of super-B reported recently, is being explored as an anode material in alkali metal (Li, Na, and K) ion batteries. After adsorption of AM (Li, Na, and K) concentration, the metallic behavior of the super-B remains preserved even at the maximum level. The hollow site (H) appeared as a favorable site among all studied sites for adsorption metal-ion on super-B. Alkali metals adsorption on super-B yielded maximal theoretical capacities of 3718 mhAg −1 . The open-circuit voltage (OCV) was found 0.35, 0.81 and 1.39 V for AM (Li, Na, and K) decorated super-B. Furthermore, the lower diffusion barrier was calculated for Li (0.14 eV) and K (0.44 eV) along with the H-T-H, while 0.16 eV for Na along with the H-B-H site. The lower OCV, ultra-fast diffusion barrier, and high specific theoretical capacity show that this newly discovered super-B is a promising candidate to be utilized as an anode material in metal-ion batteries.